2016
DOI: 10.1097/ta.0000000000001147
|View full text |Cite
|
Sign up to set email alerts
|

Posterior paramedian subrhomboidal analgesia versus thoracic epidural analgesia for pain control in patients with multiple rib fractures

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Conceivably, the use of more peripheral regional anesthesia approaches might provide better pain control than EA. Examples include the posterior paramedian sub rhomboidal block [34] and the erector spinae plane block [35]. However, data on these two methods are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the use of more peripheral regional anesthesia approaches might provide better pain control than EA. Examples include the posterior paramedian sub rhomboidal block [34] and the erector spinae plane block [35]. However, data on these two methods are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, when compared to EA, showed a similar analgesic profile; moreover, it can be used in patients with either brain trauma, vertebral and spinal cord injury (1,16).…”
Section: Sub-rhomboidal Analgesiamentioning
confidence: 93%
“…Easier to perform than thoracic EA, it can also be performed in patients heavily sedated or with a low Glasgow Coma Scale because of the absent danger of spinal cord injury and a very low incidence of hypotension because of the unilateral sympathetic block (1,2,8,13,16).…”
Section: Pvbmentioning
confidence: 99%
“…1). The first described technique involved surface landmark-guided insertion of a tunnelled multi-orifice catheter into this plane, to provide 'continuous intercostal nerve' blockade for rib fractures [111,112]. The same technique (under a different name) was used in another non-randomised comparative study of rib fractures which demonstrated equivalent analgesia compared with thoracic epidural anaesthesia [113].…”
Section: Posterior Chest Wallmentioning
confidence: 99%